2004 7th Grade Social Studies Curriculum and Historical Consciousness - Cakmak, Zafer; Bulut, Birol (Pamukkale Univ, 2013)
Social studies; which takes people and their life as a subject to itself helps to people to recognise theirself and others and also intends to give sufficient information to balance individual needs and social ecpectations. In Social studies history carries a special importance for individual and society in the name of socialization of individual. Because human; must learn values of his/her own social culture, must build his/her own consciousness, in a phrase for socialization of individual and knowing the society history is the only way for it. Having historical consciousness is equal with knowing what is the being human which helps to understand yesterday, fulfill today with experiences and being prepared for tomorrow, this is also only way being conscious and being active member of society. This investigation intends to show importance of historical consciousness with blending it with the subjects within social sciences and their teaching among the Social studies of 7th grade. Results we got from the investigation of subjects of 7th grade Social studies curriculum shows that is has great efficiency through historical consciousness with its current status.
Keywords: Social Studies History; Historical Consciousness; History Teaching